Varicella Zoster Virus reactivation causing meningitis in a 12-year-old immunocompetent girl, a case report - Van der Auwera, Tessa; Pattyn, Luc; Van Roest , Aalt (Belgian Journal of Paediatrics, 2024)
Varicella-zoster virus (VZV) presents as chickenpox during primary infection. The virus becomes dormant in the dorsal root ganglia and can reactivate. Neurological complications of VZV reactivation have been described and may present without the typical herpes zoster rash. We present a case of a 12-year-old girl with persistent headache, photophobia, nausea, and vomiting. Cerebrospinal fluid showed lymphocytic pleocytosis and positive PCR for VZV. VZV meningitis is a rare diagnosis in immunocompetent children. However, our case suggests that sudden onset and persistent headache may rarely be caused by reactivation of VZV, even in the absence of a typical rash.